Analysis of the possibilities for establishing inter-branch organisations - Republic of North Macedonia case study - VOICILAS Dan-Marius; Nacka, Marina (Agrociencia, 2020)
The Inter-branch organisations (IBO) are the highest forms of organisations for agricultural producers, together with other actors involved in the chain of the product. At European Union (EU) level, there are strict regulations as regards IBO and the member states are in different stages of implementation. Also, there are non-member states of EU that wish to establish IBO according to EU rules, because they want to sell their products on EU market and the present regulations do not accept them. This is the case of the Republic of North Macedonia (RNM). The paper presents the analysis of the current state of the process for establishing of IBO for apples in RNM having in view the initiative of producers and the possible scenarios. Data were collected from the available literature, through field surveys and in-depth interviews with stakeholders, in cooperation with the Ministry of Agriculture, based on the EU funded project “Introduction and Implementation of CMO measures”, EuropeAid/139105/DH/SER/MK. The results show the main opportunities and constraints for the actors involved in this process, based on SWOT analysis and the directions that the producers and the authorities must follow to establish IBO, also the best scenario accessible for implementation.
Keywords: Inter-branch organisations, Trade, Agricultural policy, Apples, Republic of North Macedonia.